Bringing MRI to Low- and Middle- Income Countries: Directions, Challenges and Potential Solutions - Adeleke, Sola; Murali, Sanjana; Ding, Hao; Adedeji, Fope; Qin, Cathy; Obungoloch, Johnes; Sirkis, Tamir; Asllani, Iris; Ntusi, Ntobeko A. B.; Mammen, Regina; Anazodo, Udunna; Niendorf, Thoralf (NMR in Biomedicine, 2023)
The global disparity of magnetic resonance imaging (MRI) is a well-known problem but often under-reported with many low- and middle-income countries (LMICs) experiencing limited access to MRI. Reasons for limited access include technological, economic, and social factors. With these limitations in mind, we describe a framework of solutions to tackling different aspects of MRI development in low- and middle-income countries.
Keywords: Global disparity; MRI; Solutions; Low- and middle-income countries